Bioenergy governance between market and government failures: A new institutional economics perspective - Alexandra Purkus; Erik Gawel; Daniela Thrän (Helmholtz-Zentrum für Umweltforschung (UFZ), 2012)
Bioenergy can play an important part in managing the transition towards a lowcarbon energy system. However, in many countries its rapid expansion increases pressures on agricultural land use and natural ecosystems, resulting in conflicts with conservation aims and food security. Establishing an effective governance framework for bioenergy, to safeguard against sustainability risks and promote the efficient use of scarce biomass resources, is of the utmost importance, but is complicated by the existence of multiple objectives, multiple market failures and the variety of possible value chains. In this situation, policy recommendations based on neoclassical assumptions prove too abstract to be of practical relevance. Using the case of European bioenergy policy, this paper explores how economic bioenergy policy recommendations could be improved by using a new institutional economics (NIE) perspective. Moving along the value chain, we discuss what implications the consideration of transaction costs, incomplete information, path dependencies, and political feasibility has for finding solutions to the governance challenges of bioenergy. We conclude that policy implications derived from NIE differ clearly both from neoclassical recommendations and current EU bioenergy policy, and that a NIE framework for the analysis of bioenergy governance, which takes not only market failures, but also the risks of government failures into account, could make a useful contribution to the development of realistic, second-best solutions to the allocative problems of bioenergy use.
Keywords: 330; bioenergy policy; renewable energy policy; climate change mitigation; new institutional economics